2006
DOI: 10.14411/eje.2006.106
|View full text |Cite
|
Sign up to set email alerts
|

Western flower thrips (Thysanoptera: Thripidae) preference for thrips-damaged leaves over fresh leaves enables uptake of symbiotic gut bacteria

Abstract: Abstract.To understand the evolution of insect gut symbionts it is important to determine how they are passed on to the next generation. We studied this process in Erwinia species bacteria that inhabit the gut of western flower thrips, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae). This is a polyphagous herbivore and a world-wide pest in agricultural crops. With bacteria in the gut, the thrips larval development time can be shorter and its oviposition rate higher compared to bacteria-free thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…For instance, Felkey and collaborators [40] reported the inefficacy of sodium hypochlorite to eliminate contamination of Salmonella from stem scars and wounded tomato fruits. Interestingly, the preference of thrips for thrips-damaged leaves over fresh leaves has been previously reported as a mechanism that enables the uptake of symbiotic gut bacteria [41]. In our study, significant S. enterica populations were recovered from F. occidentalis -damaged areas of lettuce leaves.…”
Section: Discussionsupporting
confidence: 52%
“…For instance, Felkey and collaborators [40] reported the inefficacy of sodium hypochlorite to eliminate contamination of Salmonella from stem scars and wounded tomato fruits. Interestingly, the preference of thrips for thrips-damaged leaves over fresh leaves has been previously reported as a mechanism that enables the uptake of symbiotic gut bacteria [41]. In our study, significant S. enterica populations were recovered from F. occidentalis -damaged areas of lettuce leaves.…”
Section: Discussionsupporting
confidence: 52%
“…Our results suggest this may also be the case for S. dorsalis . In Frankliniella occidentalis , a geographically ubiquitous association with a near Erwinia species provisionally identified as Pantoea agglomerans , is promoted behaviorally since thrips individuals prefer thrips-damaged leaves (de Vries et al 2006). Future work should investigate whether any of the dominant bacteria identified in S. dorsalis could be maintained in a similar fashion as this could provide a mechanism for the spread of transfected bacteria through the thrips population for the purpose of biological control.…”
Section: Resultsmentioning
confidence: 99%
“…Thrips on the whole have received little attention regarding this important aspect of arthropod ecology. Previous work has largely focused on the most frequently encountered bacterium (identified as a near- Erwinia species) within a single thrips species, the Western flower thrips Frankliniella occidentalis (de Vries et al 2001a; de Vries et al 2001b; de Vries et al 2004; de Vries et al 2006; Chanbusarakum & Ullman 2008, 2009; de Vries et al 2012) with a few studies on other species (Wells et al 2002; Gitaitis et al 2003; de Vries et al 2008). …”
mentioning
confidence: 99%
“…From the current study it could be argued that F. occidentalis was more attracted to undamaged plants over herbivore damaged plants as a result of induced resistance. However De Vries et al [34] showed that F. occidentalis damaged bean and cucumber plants were more attractive to conspecific females than undamaged plants. This provides further evidence for the context, or system, specificity of such interactions and highlights the danger of broader scale interpretation without specific testing.…”
Section: Discussionmentioning
confidence: 99%